2016
DOI: 10.3928/01477447-20160427-02
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Training Improves Surgical Proficiency and Safety During Diagnostic Shoulder Arthroscopy Performed by Residents

Abstract: Although virtual reality simulators have established construct validity, no studies have proven transfer of skills from a simulator to improved in vivo surgical skill. The current authors hypothesized that simulation training would improve residents' basic arthroscopic performance and safety. Twenty-two orthopedic surgery trainees were randomized into simulation or standard practice groups. At baseline testing, all of the participants performed simulator-based testing and a supervised, in vivo diagnostic shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 15 publications
2
98
0
Order By: Relevance
“…5,6 Previous investigations have generally supported some degree of skill transfer from practice on arthroscopic simulator models to performance on either cadaveric models or live arthroscopy. [7][8][9][10][11][12][13][14][15][16][17][18] However, some investigations have challenged the idea that simulator training provides generalizable skill acquisition. 19,20 In addition, the questions of how much simulator training is necessary and if there is an upper limit to the benefits of simulator training hold particular importance as new simulator technologies are being integrated into residency training programs.…”
mentioning
confidence: 99%
“…5,6 Previous investigations have generally supported some degree of skill transfer from practice on arthroscopic simulator models to performance on either cadaveric models or live arthroscopy. [7][8][9][10][11][12][13][14][15][16][17][18] However, some investigations have challenged the idea that simulator training provides generalizable skill acquisition. 19,20 In addition, the questions of how much simulator training is necessary and if there is an upper limit to the benefits of simulator training hold particular importance as new simulator technologies are being integrated into residency training programs.…”
mentioning
confidence: 99%
“…A small number of studies have attempted to assess the concurrent validity of several VR simulators, with positive results (Table IV). [43][44][45][46][47] Cannon et al 43 showed orthopaedic residents who had undergone VR simulator training outperformed their control group counterparts at probing scale scores and self-defined global rating scale scores during diagnostic knee arthroscopy in vivo. However, procedural checklist scores were not shown to be significantly different, which has been attributed to the influence of an extreme outlier.…”
Section: Resultsmentioning
confidence: 99%
“…However, procedural checklist scores were not shown to be significantly different, which has been attributed to the influence of an extreme outlier. These benefits in knee arthroscopy were also assessed by Camp et al, 45 who compared the improvements in performance to those seen in another group trained on cadaveric specimens. Contrary to these promising results, Rebolledo et al 46 reported no significant benefit derived from two and a half hours of knee arthroscopy simulation training in orthopaedic residents whose performance was subsequently assessed on cadaveric models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ó Tool (ASSET) 3,9 and patient-reported outcomes in the study design, it may actually be possible to prove what simulator enthusiasts have postulated all alongdthat simulator training does have the potential to improve surgical outcomes. [10][11][12] So, the next time you are in the operating room observing or assisting with an arthroscopic procedure, do not just watch the monitor. Look at the surgeon's arm motion and see if you can distinguish between the maestro and the novice!…”
Section: Such As the Arthroscopic Surgery Skill Evaluationmentioning
confidence: 99%